Teaching Resources: The Koreas: 1950-2020 - EAA Editorial Office (Education About Asia, 2020)
Numerous useful resources for teaching the Koreas are available in the EAA archives but the following sample should be especially helpful to history, political science, and economics instructors as teacher resources and student readings
Keywords: Education; History; Korea; North Korea; Northeast Asia; South Korea